Respuesta :
Aver si es lo que buscas!
5x(x+2) + 6 = 3
5x² + 10x + 3 = 0
x² + 2x + 3/5 = 0
- b +- (b² - 4ac)^(1/2)
------------------------------
2a
x = - 0.367544
x = - 1.63246
5x(x+2) + 6 = 3
5x² + 10x + 3 = 0
x² + 2x + 3/5 = 0
- b +- (b² - 4ac)^(1/2)
------------------------------
2a
x = - 0.367544
x = - 1.63246
5x(x+2) + 6 = 3 ................. Prop. distributiva
5x² + 10x + 6 = 3
5x² + 10x + 3 = 0
Aplicas formula general:
____________
x = -10 ± √ 100 - 4(5)(3)
2(5)
x = -10 ± √40
10
x = -1 ± √(40/100)
____
x = -1 ± √(2/5)
⇒ x1 = -1 - √(2/5) ← Primera solución
⇒ x2 = -1 + √(2/5) ← Segunda solución.
Eso es todo ;)
5x² + 10x + 6 = 3
5x² + 10x + 3 = 0
Aplicas formula general:
____________
x = -10 ± √ 100 - 4(5)(3)
2(5)
x = -10 ± √40
10
x = -1 ± √(40/100)
____
x = -1 ± √(2/5)
⇒ x1 = -1 - √(2/5) ← Primera solución
⇒ x2 = -1 + √(2/5) ← Segunda solución.
Eso es todo ;)